Biomimetic Chitin–Silk Hybrids: An Optically Transparent Structural Platform for Wearable Devices and Advanced Electronics. (4th December 2017) - Hong, Moo‐Seok; Choi, Gwang‐Mun; Kim, Joohee; Jang, Jiuk; Choi, Byeongwook; Kim, Joong‐Kwon; Jeong, Seunghwan; Leem, Seongmin; Kwon, Hee‐Young; Hwang, Hyun‐Bin; Im, Hyeon‐Gyun; Park, Jang‐Ung; et al.
Abstract: The cuticles of insects and marine crustaceans are fascinating models for man‐made advanced functional composites. The excellent mechanical properties of these biological structures rest on the exquisite self‐assembly of natural ingredients, such as biominerals, polysaccharides, and proteins. Among them, the two commonly found building blocks in the model biocomposites are chitin nanofibers and silk‐like proteins with β‐sheet structure. Despite being wholly organic, the chitinous protein complex plays a key role for the biocomposites by contributing to the overall mechanical robustness and structural integrity. Moreover, the chitinous protein complex alone without biominerals is optically transparent (e.g., dragonfly wings), thereby making it a brilliant model material system for engineering applications where optical transparency is essentially required. Here, inspired by the chitinous protein complex of arthropods cuticles, an optically transparent biomimetic composite that hybridizes chitin nanofibers and silk fibroin (β‐sheet) is introduced, and its potential as a biocompatible structural platform for emerging wearable devices (e.g., smart contact lenses) and advanced displays (e.g., transparent plastic cover window) is demonstrated. Abstract : An optically transparent biomimetic hybrid material consisting of chitin nanofibers and silk fibroin is reported and its use as a biocompatible structural platform for emerging wearable devices (e.g., smart contact lenses) and advanced electronics (e.g., display cover window) is demonstrated.